2014
DOI: 10.1111/jdi.12200
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum CA19‐9 is associated with improvement of insulin resistance and metabolic control in patients with obesity and type 2 diabetes after Roux‐en‐Y gastric bypass

Abstract: Aims/IntroductionPatients with type 2 diabetes are known to show elevated serum levels of carbohydrate antigen 19-9 (CA19-9). The aim of the present study was to investigate the possible relationships of CA19-9 with metabolic control, insulin resistance (IR), and pancreatic β-cell function in patients with obesity and type 2 diabetes who underwent Roux-En-Y gastric bypass (RYGB).Materials and MethodsThe present study included 81 healthy volunteers, and 33 patients diagnosed with obesity and type 2 diabetes who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Esteghamati et al 31 reported significant associations of CA19-9 with HbA1c and insulin resistance, and these associations were persistent in subjects with diabetes but not in those without diabetes. Tu et al 32 found that insulin resistance is an important contributing factor in the changes in serum levels of CA19-9 after rapid metabolic control by Roux-en-Y gastric bypass. Since glucose toxicity is associated with insulin resistance and changes in the serum levels of CA19-9, 61 the association between elevated CA19-9 and hyperglycemia might be involved in the mechanisms of both beta-cell dysfunction and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esteghamati et al 31 reported significant associations of CA19-9 with HbA1c and insulin resistance, and these associations were persistent in subjects with diabetes but not in those without diabetes. Tu et al 32 found that insulin resistance is an important contributing factor in the changes in serum levels of CA19-9 after rapid metabolic control by Roux-en-Y gastric bypass. Since glucose toxicity is associated with insulin resistance and changes in the serum levels of CA19-9, 61 the association between elevated CA19-9 and hyperglycemia might be involved in the mechanisms of both beta-cell dysfunction and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…22 Numerous studies have reported that circulating CA19-9 is elevated during hyperglycemia in patients with diabetes. [23][24][25][26][27][28][29][30][31][32] CA19-9 levels were revealed to be associated with hemoglobin A1c (HbA1c) and fasting blood glucose and to be decreased after improvement of glycemic control. 28,33 The mechanism of elevated serum CA19-9 in diabetic patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher cut-off value of 75 U/mL would result in an increase of false-negatives. It has been reported that an elevated serum levels of CA19-9 in patients with diabetes were decreased within 2 weeks by improvement of glycemic control [10,15,16]. Therefore, when serum CA 19-9 is between 37 and 75 U/mL, it would seem reasonable to re-examine the patient at least 2 weeks after • cut-off value of CA19-9 with the maximum sensitivity + specificity for predicting pancreatic cancer (75 U/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is also associated with an increased risk of pancreatic cancer [6]. However, the serum level of CA19-9 is elevated in patients with poorly controlled diabetes [7][8][9], while it is normalized by improvement of glycemic control [10,11]. Thus, serum CA19-9 exceeds 37 U/mL in some patients with diabetes although they do not have pancreatic cancer.…”
mentioning
confidence: 99%